Analysis and Forecast of the Development of the Pet Industry in China and Globally Based on ARIMAX and Regression Models - Chang, Zhenjia; Wei, Yuan (Transactions on Computer Science and Intelligent Systems Research, 2025)
This paper systematically analyses the development trends of the pet industry in China and globally based on the ARIMAX model and various regression models. The study first collects data on the number of pets in China and influencing factors such as GDP and population. It then uses the ARIMAX (p,d,q) model combined with the AIC criterion to determine parameters, constructs a multi-factor regression model to analyse key influencing factors, and predicts trends. For the global market, data from major regions were collected, and linear extrapolation and multiple linear regression models were used to analyse the mechanisms underlying key factors and predict demand scale. At the supply-demand level, linear and exponential regression models were employed to explore the interdependent relationships between domestic demand, export volumes, and the global market. Throughout the study, the cross-application of ARIMAX models and various regression models systematically revealed the key influencing factors and trends in this field, with model fitting results validating the reliability of the research conclusions.